Encoding Information From Rotations Too Rapid To Be Consciously Perceived as Rotating: A Replication of the Motion Bridging Effect on a Liquid Crystal Display. (May 2020) - Stein, Maximilian; Fendrich, Robert; Mattler, Uwe
Abstract: A ring of points that is rotated so rapidly is perceived as a stationary outline circle that can induce an illusory rotation with the same spin direction in a subsequently presented ring of stationary points. This motion bridging effect (MBE) demonstrates that motion information can be conveyed by temporal frequencies generally thought to exceed the processing capabilities of the human visual system. It was first described in displays shown with an analog oscilloscope, but the rapid rotation rates needed to produce the MBE have heretofore prevented it from being investigated with conventional raster scan monitors. Here, we demonstrate the MBE can be reliably generated using the new generation of 240 Hz LCD gaming monitors, and exhibits basic characteristics similar to those reported previously. These monitors therefore provide a readily available resource for research on the MBE and the studies of the visual processing rapid motions in general.